LPS Modulates the Expression of Iron-Related Immune Genes in Two Antarctic Notothenoids - Martínez, Danixa Pamela; Sousa, Carmen; Oyarzún, Ricardo; Pontigo, Juan Pablo; Canario, Adelino V. M.; Power, Deborah Mary; Vargas-Chacoff, Luis; Guerreiro, Pedro Miguel (Frontiers in Physiology, 2020)
Abstract The non-specific immunity can induce iron deprivation as a defense mechanism against potential bacterial pathogens, but little information is available as to its role in Antarctic fish. In this study the response of iron metabolism related genes was evaluated in liver and head kidney of the Antarctic notothenoids Notothenia coriiceps and N. rossii 7 days after lipopolysaccharide (LPS) injection. Average plasma Fe2+ concentration was unaffected by treatment in any of the species. The gene expression response to LPS varied between tissues and species, being stronger in Notothenia coriiceps and more prominent in the head kidney than liver. The reaction to LPS was marked by increased individual variability in most genes analysed, even when the change in expression was not statistically significant, suggesting different individual sensitivity and coping responses in these wild fish. We found that iron related genes had an attenuated and homogenous response to LPS but there was no detectable relationship between plasma Fe2+ and gene expression. However, overall in both tissues and species LPS exposure set a multilevel response that concur to promote intracellular accumulation of iron, an indication that Antarctic Notothenoids use innate nutritional immunity as a resistance mechanism against pathogens.